Depressive Symptoms & Associated Stressors among Medical Students - Al-Kadhimi, Firas A.; Al-Hemiary, Nesif J.; Hassan, Ahmed (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Depressive symptoms are commonly occurring in many psychiatric illnesses. Many people experience the first symptoms of depression during their college years. Unfortunately, many college students who have depression are not getting the help they need. Objectives : to find out the point prevalence of clinically significant depressive symptoms in students of Baghdad College of Medicine, University of Baghdad, and its association with life stressors. Subjects and Methods: A cross sectional study of students of Baghdad College of Medicine, University of Baghdad during March and April 2013. A random sample was chosen and each student was asked to fill a questionnaire that contains demographic information, the Patient Health Questionnaire-9 (PHQ-9), Beck Depression Inventory-II (BDI-II), and the Student’s Stressors Questionnaire. Data were analyzed by using SPSS (V.18). Appropriate tests were used for significance. Results: A total of 250 students (140 females and 110 males) was surveyed which included 50 students from each year. Female to male ratio was 1.27. Their age ranged between 18–45 years and the mean age was 22.2 ±2.3.Twenty-eight percent have clinically significant depressive symptoms, 12.4% have milder form of depression according to PHQ-9. Clinical depressive symptoms found among 37.2 % (borderline clinical depression to extremely severe depression) according to BDI-II. The mean of life stressors scores was 97.98 out of 180 (SD=18.68). Educational, psychological, and environmental stressors were the most common types of stressors. There is strong statistical relationship between life stressor category and clinically significant depressive symptom (P value= 0.000). Conclusion: clinically significant depressive symptoms are common among medical students of Baghdad University. Stressors were high and are positively associated with the presence of depressive symptoms.